The characterization of the stress fields near a crack tip for a compact specimen for elastic-plastic materials dominated by the plane strain state - Graba, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a comprehensive analysis of the stress field near a crack tip for a compact specimen dominated by the plane strain state using the finite element method. The analysis also includes the calculation of some parameters of in-plane constraints, both for small and large strain assumptions. It discusses the influence of the material characteristic, relative crack length and external load for the stress field, and the in-plane constraint parameter. The approximation formulas for some in-plane constraint parameters are presented.
Keywords: fracture mechanics; C(T); stress field; FEM; constraints; plane strain; plastic zone; cracks